ARTIFICIAL INTELLIGENCE AND LANGUAGE TRANSLATION: CHALLENGES AND OPPORTUNITIES - Xojabekova , Ramzida (Scientific practical conference, 2026)
This article provides an in-depth analysis of artificial intelligence (AI) in the field of language translation, exploring both its transformative opportunities and associated challenges. It examines the evolution from statistical machine translation to neural machine translation and transformer-based models, highlighting improvements in accuracy, fluency, and contextual understanding. The article discusses key issues including translation of idiomatic expressions, low-resource languages, cultural nuance, bias, and ethical considerations related to data privacy and inclusivity. Human-AI collaboration, multimodal translation, and post-editing strategies are also explored. The study concludes that while AI significantly enhances accessibility and efficiency in translation, careful oversight, ethical data management, and human expertise remain essential to ensure accurate, culturally sensitive, and equitable translations.